EFFECTS OF DONOR HYDROGEN SULFIDE NaHS ON HEART RATE VARIABILITY IN EXPERIMENTAL ANIMALS - Iryna Kovalchuk (Праці Наукового товариства імені Шевченка. Медичні науки, 2016)
EFFECTS OF DONOR HYDROGEN SULFIDE NaHS ON HEART RATE VARIABILITY IN EXPERIMENTAL ANIMALS